Network Performance of Broadband Hosts: Measurements & Implications - Lakshminarayanan, Karthik; Padmanabhan, Venkat (2003)
With the rapid growth in the popularity of and the research interest in peer-to-peer (P2P) systems, an interesting question is what the quality of network connectivity between peers in the “real world” is and what implications this has for applications. In this paper, we describe an effort called PeerMetric to directly measure P2P network performance from the vantage point of broadband-connected residential hosts. Our measurements indicate significant asymmetry in bandwidth, with median downstream and upstream available bandwidths of 900 Kbps and 212 Kbps, respectively. We argue that the availability of last-hop bandwidth is more important than the traditional consideration of locality for overlay multicast over broadband hosts. We also considered the peer selection problem and found that a simple delay-vector based approach is effective for finding proximate peers (in terms of latency). However, P2P latency turns out to be a poor predictor of P2P TCP throughput, which may be the metric of interest for applications such as file sharing.